Traveling wildfire [compact disc] - Flemons, Dom, 1982- (Smithsonian Folkways, 2023)
Dom Flemons has built a reputation on presenting 100 years of American roots music. Carefully selected from his personal repertoire, these original songs reveal his love of country, western, blues, Americana, bluegrass and folk music as they tell of true love, family legacy, survival, time travel, and the juxtaposition between light and dark.